Control of chemical reactor for consecutive reactions I - Drábek, Oldřich; Krejčí, Stanislav (Univerzita Pardubice, 1995)
A new strategy for the control of the continuous stirred tank reactor (CSTR) with a consecutive reaction is presented. The new control strategy – the self-tuning controller is derived from the reactor behaviour in both the steady – and the transient states. The controller is briefly described and results of simulation calculations are presented.